College students' underlying perceptions of COVID-19 threat, healthcare discrimination, and healthcare system inequities associated with self-rated health across racial/ethnic groups in the U.S. - Fernandez, Jessica R.; Sherchan, Juliana S.; Cho, Yong Ju; Nanaw, Judy; Joseph, Nataria T.; Forde, Allana T. (Frontiers in Public Health, 2023)
Background: COVID-19-related health perceptions may differentially impact college students’ stress, and in turn, their mental and physical health. This study examined racial/ethnic differences in college students’ underlying perceptions of COVID-19 threat and U.S. healthcare inequities and their associations with self-rated mental and physical health. Methods: Four-hundred-thirty-two university students completed an online survey (December 2020-December 2021). Latent class analyses identified classes of perceived COVID-19 threat (i.e., severity, susceptibility), healthcare discrimination, and U.S. healthcare system inequities. Regression analyses examined whether class membership varied by race/ethnicity and was associated with self-rated mental and physical health. Results: Class 1 members (27.3% of sample) were more likely to identify as Hispanic or Latino, Non-Hispanic Asian, Non-Hispanic Black or African American, and Non-Hispanic Multiracial versus Non-Hispanic White (versus Class 4). Class 1 had high perceived COVID-19 threat, medium perceived healthcare discrimination, and high perceived healthcare system inequities, as well as higher odds of poorer mental and physical health (versus Class 4). Conclusions: College students’ underlying perceptions of high COVID-19 threat and healthcare inequities were associated with poorer health. Given students with these perceptions were more likely to belong to racial/ethnic minority groups, concerns over COVID-19 risk and healthcare may partially explain racial/ethnic disparities in college students’ health. This study contributes to a limited body of evidence on college students’ perceptions of the U.S. healthcare system and suggests important ways that structural inequalities and racial/ethnic disparities in COVID-19 risk, healthcare discrimination, and concerns over U.S. healthcare system inequity may affect college students’ health.